Diagnosis and prognosis of turbomachinery vibrations - Ming Chen, H.; Malanoski, S. B. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Vibration analysis is rapidly becoming a requirement rather than al luxury in turbomachinary development and implementation. Presented herein is a discussion on rotating equipment vibration problems - their occurrence, their diagnosis by analytical and experimental methods, and a look to the future in this area.